Antidepressant medication use, weight gain, and risk of type 2 diabetes: a population-based study. - Kivimäki, M; Hamer, M; Batty, G; Geddes, JR; Tabak, A; Pentti, J; Virtanen, M; Vahtera, J (2010)
OBJECTIVE: To examine antidepressant medication use as a risk factor for type 2 diabetes and weight gain. RESEARCH DESIGN AND METHODS: A series of nested studies within a prospective cohort of 151,347 working-aged men and women including 9,197 participants with continuing antidepressant medication, 224 with severe depression, and 851 with incident type 2 diabetes during a mean follow-up of 4.8 years, as indicated by national health and prescription registers (the Public Sector study, Finland 1995-2005). RESULTS: In the first analysis, the case subjects were individuals with incident type 2 diabetes compared with matched diabetes-free control subjects. Antidepressant use of ≥ 200 defined daily doses was associated with a doubling of diabetes risk in both participants with no indication of severe depression (odds ratio 1.93 [95% CI 1.48-2.51]) and participants with severe depression (2.65 [1.31-5.39]). In further analyses, the exposed group was antidepressant users and the reference group was nonusers matched for depression-related characteristics. The 5-year absolute risk of diabetes was 1.1% for nonusers, 1.7% for individuals treated with 200-399 defined daily doses a year, and 2.3% for those with ≥ 400 defined daily doses (P(trend) < 0.0001). An average self-reported weight gain, based on repeated surveys, was 1.4 kg (2.5%) among nonusers and 2.5 kg (4.3%) among users of ≥ 200 defined daily doses (P(trend) < 0.0001). Separate analyses for tricyclic antidepressants and selective serotonin reuptake inhibitors replicated these findings. CONCLUSIONS: In these data, continuing use of antidepressant medication was associated with an increased relative risk of type 2 diabetes, although the elevation in absolute risk was modest.